(untitled) (Journal of the College of Basic Education, 2022)
The nature of this research (The Phenomenon of Revelation in Islamic Reception) necessitated that it be divided, after this introduction, into four sections:As for the first topic: it is (revelation, its concept, its images), in which I explained: first: the concept of revelation in language and idiomatically, and second: the images of divine revelation.As for the second topic: (The characteristic of Gabriel, peace be upon him, and the manner of his revelation), it included the description and manner of his revelation, may God’s prayers and peace be upon him, from what was mentioned in the Holy Qur’an and Islamic narratives.As for the third topic: (The first and last of the Qur’anic revelation), I explained in it the statements of the scholars and their differences in explaining the first and last of the divine revelation.As for the fourth topic: (The Meccan and Civil Revelation), in it I dealt with the Meccan and the Civilian, and the way to know them, as well as the statement of the Meccan and Civilian signs.